The midwifery care for pregnant mother tm lll with physiological vaginal discharge at Gondokusuman Health Center I Baciro Yogyakarta - Enny Fitriahadi; Yessi Priskila (Universitas 'Aisyiyah Yogyakarta, 2019)
The purpose of this research was to be able to provide midwifery care for pregnant women with third trimester physiological vaginal discharge at Gondokusuman Health Center I Yogyakarta. The research design used descriptive observational method and observational approach. The sampling technique in this study used accidental sampling method with a sample of third trimester pregnant women who experienced physiological vaginal discharge and used picot analysis. The results of this study after a visit for 3 times and given a counseling intervention about personal hygiene and maternal hygiene in caring for women, complaints of physiological vaginal discharge in third trimester pregnant women can be resolved. The suggestions for pregnant women should always be routine and regular in doing personal hygiene and taking care of their feminine area properly.